2018
DOI: 10.1161/circulationaha.117.029930
|View full text |Cite
|
Sign up to set email alerts
|

NMDA-Type Glutamate Receptor Activation Promotes Vascular Remodeling and Pulmonary Arterial Hypertension

Abstract: These results reveal a dysregulation of the glutamate-NMDAR axis in the pulmonary arteries of patients with PAH and identify vascular NMDARs as targets for antiremodeling treatments in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 61 publications
4
73
0
Order By: Relevance
“…Notably, the YAP/TAZ-GLS1 axis induced glutaminolysis in SIV-induced PAH primates as well as in HIV-infected PAH patients, suggesting a mechanistic link between glutaminolysis and this enigmatic PAH subtype. Building on these findings, a separate study demonstrated that elevated glutamate, following GLS1-mediated conversion of glutamine, stimulated NMDA-type glutamate receptors, induced glutamatergic cell-cell signaling in pulmonary vessels, and promoted PH (46). Aberrant glutamine metabolism represents an increasingly promising diagnostic and therapeutic target in PH, given its fundamental roles in promoting proliferative capacity and potentially mediating pathogenic cell-cell interactions.…”
Section: R E V I E W S E R I E S : M I T O C H O N D R I a L D Y S F mentioning
confidence: 93%
“…Notably, the YAP/TAZ-GLS1 axis induced glutaminolysis in SIV-induced PAH primates as well as in HIV-infected PAH patients, suggesting a mechanistic link between glutaminolysis and this enigmatic PAH subtype. Building on these findings, a separate study demonstrated that elevated glutamate, following GLS1-mediated conversion of glutamine, stimulated NMDA-type glutamate receptors, induced glutamatergic cell-cell signaling in pulmonary vessels, and promoted PH (46). Aberrant glutamine metabolism represents an increasingly promising diagnostic and therapeutic target in PH, given its fundamental roles in promoting proliferative capacity and potentially mediating pathogenic cell-cell interactions.…”
Section: R E V I E W S E R I E S : M I T O C H O N D R I a L D Y S F mentioning
confidence: 93%
“…The NMDAR, a major glutamate receptor of excitatory neuronal synapses, is an ion channel receptor also expressed in PASMC and pulmonary arterial ECs [ 133 ]. NMDARs are a class of ionotropic glutamate receptors that also includes the AMPA receptors and kainate receptors.…”
Section: Functional and Molecular Classification Of Ion Channels Imentioning
confidence: 99%
“…Recently, NMDAR expression was demonstrated in human and rodent pulmonary vascular cells [ 133 ], which contributes to vascular cell proliferation and angiogenesis. In PAH, glutamate (a NMDAR agonist) is accumulated in pulmonary arteries from PAH patients.…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations